Teachers’ Perception Towards The Use of Tarsia Puzzle to Create Joyful Learning of Mathematics - Nur Qomaria (Vygotsky : Jurnal Pendidikan Matematika dan Matematika, 2021)
This research aims to determine whether Tarsia puzzle can be used to create joyful learning of mathematics according to elementary school teachers’ perception.Fortytwo elementary school teachers who teach at different schools in Bangkalan, Madura were surveyed. In this survey research, data about teachers’ perception were collected usinga questionnaire with 16 close-ended items (Likert Scale 1 – 4). Descriptive statistics consisting of percentages and means were used to analyze the data. The results showed that teachers agreed that Tarsia puzzle can help teachers to create joyfullearning of mathematics in elementary school.However, some of them stated that they had lack confidence and competence in using Formulator Tarsia.